Why do good people do bad things?. Issue 1 (June 2015) - Venditti, Ellen Grady
<x xml:space="preserve">Abstract</x> That was the question Dr. Lucien Leape, patient safety pioneer, posed in the title of a lecture he delivered at a Harvard University risk management conference way back in 1997. As a new healthcare risk manager, I had been asking myself this same question almost every day since my move from nursing to risk management.